A Philosophical Understanding of the Arabic Language Acquisition Process in Early Childhood: A Philosophy of Language Perspective and its Implications for Teaching Methods - Zulfida, Sri; Zuriyati, Zuriyati; Setiadi, Samsi (Universitas Muhammadiyah Sumatera Barat, 2024)
This research examines the application of philosophy of language in early childhood Arabic language acquisition, focusing on pragmatics, semantics, and hermeneutics. Using a qualitative approach with descriptive methods, the research involved observations and interviews in three Raudhatul Athfal in Riau Islands. The results showed that the pragmatic approach that integrates real-life contexts, such as role-playing, is effective in improving communication skills. The semantic approach, through the introduction of real object-based vocabulary, strengthens children's understanding of meaning structures. Meanwhile, hermeneutics helps children internalise cultural and religious values through interactive stories and daily prayers. Although challenges such as lack of social environmental support and semantic complexity were encountered, great opportunities emerged through educational technology innovation and community collaboration. This research makes a theoretical contribution in the integration of philosophy of language with Arabic language teaching, as well as offering practical guidance for designing more effective and meaningful teaching methods.